Le rôle du verbe dans le réseau dérivationnel des prédicats nominaux - Vetulani, Grażyna (Studia Romanica Posnaniensia, 2004)
The paper focuses on the category of verb and more specifically on support verbs which form compound predicates with abstract nouns. We discuss various functions of verbs within the language system and the role of the support verb in compound predicative expressions. We observe numerous cases where different verbs may co-occur with one and the same abstract noun. The substitution of one support verb for another partially or totally changes the meaning of the whole compound predicative expression. Analysis of such cases may be useful for studying different meanings of nouns.